E-Government for good governance in developing countries : empirical evidence from the eFez Project - Kettani, Driss (London : Anthem Press, 2014)
Drawing lessons from the eFez Project in Morocco, this volume offers practical supporting material to decision makers in developing countries on information and communication technologies for development (ICT4D), specifically e-government implementation. The book documents the eFez Project experience in all of its aspects, presenting the project's findings and the practical methods developed by the authors (a roadmap, impact assessment framework, design issues, lessons learned and best practices) in their systematic quest to turn eFez's indigenous experimentations and findings into a formal framework for academics, practitioners and decision makers. The volume also reviews, analyzes and synthesizes the findings of other projects to offer a comparative study of the eFez framework and a number of other e-government frameworks from the growing literature.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).